Evaluation of Patient Satisfaction, Preference and Side Effects after Annual Zoledronic Acid Infusion in Patients with Osteoporosis - Banu Dilek; Ebru Şahin; Didem Erdem; Deniz Bulut; Selmin Gülbahar (Galenos Yayinevi, 2017)
Objective: In this study it was aimed to evaluate the patient satisfaction, therapy preference and side-effect profile in patients who receive annual zoledronic acid (ZA) infusion. Materials and Methods: In this study, 59 patients who had ZA infusion were enrolled. Their demographic and osteoporosis characteristics and the number of received ZA infusions were recorded. A seven-item questionnaire was used to assess the patients' therapy preference. General patient satisfaction, satisfaction during ZA infusion and its effects on life quality were assessed with a Likert scale. Results: The mean age of the 59 patients (50 females, 9 males) was 68.49±8.65 years. Of the patients 86.4% (51) wanted to continue the same therapy, 64.4% (36) stated that the mode of administration was very convenient and 61% (36) stated that it was well-suited with their lifestyle. The most important factors for the continued usage were the annual administration convenience and the physician's recommendation. Mild side effects (myalgia, arthralgia, flu-like syndrome, fever, headache and pruritus) were reported in 23.7% of the patients (14) subsequent to the first infusion. ZA infusion was quite satisfying for 37.3% of the patients (22) and very satisfying for 40.7% of the patients (24). When the treatment effect on the quality of life was investigated, 42.4% of the patients (25) found it very effective, while 37.3% of them (22) found it extremely effective. Among these patients, 47.5% received their first ZA infusion (28), while 52.5% received multiple (2-4) infusions before (31). The increasing number of infusions did not have any influence on the patient's life quality, satisfaction or therapy preference. Conclusion: ZA infusion is a preferable, highly satisfactory, convenient therapy and its side effects are well-tolerated, it affects the quality of life favourably.